The Effect Of Discounts, Free Shipping And Cash On Delivery On Purchasing Decisions With Purchase Intention As An Intervening Variable In The Shopee Marketplace - Hendra Setiawan; Elsa Widya Wati (Citakonsultindo, 2024)
This study is entitled “The Effect of Discounts, Free Shipping, Cash On Delivery on Purchasing Decisions with Purchase Interest as an Intervening Variable in the Shopee Marketplace” The purpose of the study was to determine whether there is an effect of discounts, free shipping, Cash On Delivery on purchasing decisions and purchase interest. As well as the indirect effect of discounts, free shipping, Cash On Delivery on purchasing decisions with buying interest as an intervening variable (case study of Distro Monkey Ceria consumers). This research was conducted at Distro Monkey Ceria on shopee. The research sample was 385 respondents. The research method used is a quantitative approach using SmartPLS software version 4.0. The results of this study indicate that. Discounts, Free shipping, Cash On Delivery, have a positive effect on buying interest. Discounts and free shipping have no positive effect on purchasing decisions. Cash On Delivery and buying interest have a positive effect on purchasing decisions. Discounts, Free Shipping and Cash On Delivery have a positive effect on purchasing decisions through buying interest.